Stock Market’s Contribution on Economic Growth in Nepal: A Brief Note - Shah, Ram Khelawan (Journal of Development and Administrative Studies, 2017)
This paper aims to examine the relation between stock market development and economic growth in Nepal for period of mid July 2001 to mid-July 2015 by using Karl Pearson correlation. The whole study period is divided into two parts, first stage and second stage of stock market development. The study finds that in the first stage- mid July 2001 to mid- July 2007, stock market development was not significantly associated with economic growth. In second stage-mid July 2008 to mid-July 2015 there is positive relation between stock market development and economic growth. The findings indicate that stock market has positive contribution on economic growth in Nepal.